FUNGSI PARTAI POLITIK DALAM MENINGKATKAN PARTISIPASI POLITIK DITINJAU DARI HUKUM POSITIF - Suimi Fales (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: The fact that at this time political education carried out by political parties is still very lacking. Political education is carried out only during the campaign period leading up to the election, namely voter education in terms of elections and political parties' vision and mission, this indicates that political education carried out is directed at choosing the party. The very complex relationship between social problems and political aspects makes it difficult for most citizens to understand the social dimension and the political dimension of their existence. It is also difficult to recognize political rights and their political role. The results of the study are according to Law No. 2 of 2011, that the functions of political parties are: first political education for members and the wider community to become Indonesian citizens who are aware of their rights and obligations in the life of the community, nation and state; second Creation of a climate conducive to the unity and unity of the Indonesian people for the welfare of society; thirdly Absorbers, collectors, and channelers of the people's political aspirations in formulating and determining state policies; political participation of Indonesian citizens; and fourth, political recruitment in the process of filling political positions through a democratic mechanism by paying attention to gender equality and justice.Keywords: Political Party, Participation, Law